1990
DOI: 10.1111/j.1365-2125.1990.tb03665.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent administration of omeprazole on serum pepsinogens in duodenal ulcer patients and healthy volunteers.

Abstract: 1. Omeprazole, a substituted benzimidazole inhibitor of the gastric H+/K(+)‐APT‐ase, was administered orally at a dose of 20 mg in the morning of 3 consecutive days, followed by a period of 4 days without medication, and this intermittent dosage regimen was continued for 4 weeks. 2. During intermittent administration of omeprazole to 10 patients with duodenal ulcer disease and 10 healthy volunteers concentrations of serum pepsinogen A and serum pepsinogen C were monitored by sensitive and specific radioimmunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Other experiences showed significantly higher serum pepsinogen levels after 7 and 14 days therapy with omeprazole 20 mg daily compared with pretreatment values; furthermore, a rapid fall of PGI (within 7 days) to baseline levels after discontinuing antisecretory therapy was observed [9]. Similar results were obtained after omeprazole intake for 3 consecutive days in a regimen of intermittent administration [10]. Although other reports confirmed the decrease of PGI values after interruption of long-term antisecretory therapy, PGI levels were higher than previous therapy [12].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Other experiences showed significantly higher serum pepsinogen levels after 7 and 14 days therapy with omeprazole 20 mg daily compared with pretreatment values; furthermore, a rapid fall of PGI (within 7 days) to baseline levels after discontinuing antisecretory therapy was observed [9]. Similar results were obtained after omeprazole intake for 3 consecutive days in a regimen of intermittent administration [10]. Although other reports confirmed the decrease of PGI values after interruption of long-term antisecretory therapy, PGI levels were higher than previous therapy [12].…”
Section: Discussionsupporting
confidence: 59%
“…to baseline levels after discontinuing antisecretory treatment [9][10][11][12][13][14][15][16][17][18]. It is generally accepted that serum pepsinogen I (sPGI) reflects gastric acid secretion [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not obtain data on the medications and underlying diseases of enrolled patients. Previous studies have revealed that patients taking proton pump inhibitors‍ ( 44 , 45 ) and patients with renal dysfunction‍ ( 46 ) showed significantly elevated serum PG. Such patients should have been excluded from the present study, but the present study did not have access to information on underlying diseases or medications and thus may well have included such patients.…”
Section: Discussionmentioning
confidence: 99%